Murine norovirus detection in the exhaust air of IVCs is more sensitive than serological analysis of soiled bedding sentinels. (June 2017) - Zorn, Julia; Ritter, Bärbel; Miller, Manuel; Kraus, Monika; Northrup, Emily; Brielmeier, Markus
One limitation to housing rodents in individually ventilated cages (IVCs) is the ineffectiveness of traditional health monitoring programs that test soiled bedding sentinels every quarter. Aerogen transmission does not occur with this method. Moreover, the transmission of numerous pathogens in bedding is uncertain, and sentinel susceptibility to various pathogens varies. A novel method using particle collection from samples of exhaust air was developed in this study which was also systematically compared with routine health monitoring using soiled bedding sentinels. We used our method to screen these samples for the presence of murine norovirus (MNV), a mouse pathogen highly prevalent in laboratory animal facilities. Exhaust air particles from prefilters of IVC racks with known MNV prevalence were tested by quantitative reverse transcription polymerase chain reaction (RT–qPCR). MNV was detected in exhaust air as early as one week with one MNV-positive cage per rack, while sentinels discharged MNV RNA without seroconverting. MNV was reliably and repeatedly detected in particles collected from samples of exhaust air in all seven of the three-month sampling rounds, with increasing MNV prevalence, while sentinels only seroconverted in one round. Under field conditions, routine soiled bedding sentinel health monitoring in our animal facility failed to identify 67% ( n = 85) of positive samples by RT–qPCR of exhaust air particles. Thus, this method proved to be highly sensitive and superior to soiled bedding sentinels in the reliable detection of MNV. These results represent a major breakthrough in hygiene monitoring of rodent IVC systems and contribute to the 3R principles by reducing the number of animals used and by improving experimental conditions.